A semi-universal assay platform to quantitate vaccines with potential applications for biotherapeutics. (December 2016) - Roman, Jeanette; Bouaraphan, Silikhone; Verch, Thorsten
Aim: Biologics development often requires multiple immunoassays to evaluate both assay reagents and potential drug candidates resulting in extensive analytical development.Methodology: We developed a semi-universal, 5-layer platform assay on Gyrolab using secondary antispecies or anti-isotype-specific capture and detection antibodies. We applied the assay to several multivalent vaccines.Results: Method performance exhibited a median accuracy of 110%, reproducibility of 9% CV and intermediate precision of 11% CV. System suitability criteria were met for 92.5% of the samples and only one out of 31 replicate samples exhibited a %CV greater than 20%.Conclusion: The semi-universal Gyrolab assay allowed assay development without reagent labeling. The format could also be translated into a plate-based assay.